The Pavilion of the United States (Benjamin New Co., Ltd.)
The Pavilion of the United States - on Ile Sainte Helene is a huge transparent geodesic "skybreak bubble" 250 feet in spherical diameter and 200 feet high. Its exhibits show the creative efforts of man based on a life in a prosperous and automated society.